Pelatihan Self-Regulated Learning untuk Mengatasi Prokrastinasi pada Siswa SMA BSS - Nurmala, Sukma; Mashuri, Ali (Universitas Mathla'ul Anwar Banten, 2024)
Asesmen kebutuhan pada siswa SMA kelas 10 mengidentifikasi adanya indikasi masalah prokrastinasi. Riset sebelumnya menunjukkan bahwa perilaku prokrastinasi dapat dimitigasi dengan intervensi metakognitif self-regulated learning - seberapa siswa bisa melakukan perencanaan, monitoring, dan evaluasi dalam proses belajar yang bangkit dari motivasi internal. Desain sederhana pre-test dan post-test digunakan sebagai rancangan intervensi self-regulated learning. Sebanyak 59 partisipan direkrut, diukur tingkatan pengetahuan mengenai prokrastinasi sebelum dan setelah intervensi. Conscientiousness trait juga diukur untuk mengetahui efek intervensi mengontrol pribadi rajin-teratur yang berpotensi menjadi confounding. Hasil menunjukkan main effect dari intervensi, F (1, 56) = 49,54, p < 0,001 mengontrol jenis kelamin dan perubahan Conscientiousness trait pada baseline dan post-treatment. Intervensi self-regulated learning mampu meningkatkan pengetahuan partisipan tentang prokrastinasi. Mayoritas siswa (72,9%) mengalami peningkatan pengetahuan mengenai prokrastinasi, terutama pada pengetahuan tentang strategi menangani prokrastinasi. Melalui intervensi ini, siswa lebih strategis untuk menangani isu penundaan secara mandiri. A needs assessment of 10th-grade high school students identified some indications of procrastination problems. Previous research shows that procrastination behavior can be mitigated with metacognitive self-regulated learning interventions - how much students can plan, monitor, and evaluate in the learning process that arises from internal motivation. A simple pre-test and post-test design was used as a self-regulated learning intervention plan. A total of 59 participants were recruited, and their level of knowledge regarding procrastination was measured before and after the intervention. The conscientiousness trait was also measured to determine the intervention effects control of the diligent-organized personality which has the potential to be a confounder. Results showed a main effect of the intervention, F(1, 56) = 49.54, p < 0.001 controlling for gender and changes in conscientiousness trait at baseline and posttreatment. The self-regulated learning intervention was able to increase participants' knowledge about procrastination. The majority of students (72.9%) experienced increased knowledge about procrastination, especially knowledge about strategies for dealing with procrastination. Through this intervention, students have more strategies to deal with pending problems independently.